Early maladaptive schemes and alcohol consumption in university students, according to professional career of a public university of the city of Lima - Huerta R., Rosa E. (2017)
The study has been subjected to the analysis of the variables early maladaptive schemas and alcohol consumption by career, health sciences and engineering in a sample of 510 university students, who were given a socio-demographic data sheet, the Young Schema Questionnaire composed of 18 schemes and the Alcohol Use Disorders Identification Test (AUDIT).It was found that there is a significant and positive correlation between early maladaptive schemas, emotional deprivation, insufficient self-control and recognition with alcohol consumption. In health sciences, the risk-taking group predominates the autosacrifice scheme and in engineering the schemes of Dependence / incompetence and subjugation. The students with higher risk consumption are engineering (31) compared to those in health sciences which was lower (7). Engineering students have higher alcohol consumption. Results that are serious because the alcohol consumption is associated with cognitive schemes characterized by the overestimation to the damage, low tolerance to the frustration and high necessity of social approval.